Competition × drought interactions change phenotypic plasticity and the direction of selection on Arabidopsis traits. Issue 4 (13th May 2020) - Lorts, Claire M.; Lasky, Jesse R.
Summary: Populations often exhibit genetic diversity in traits involved in responses to abiotic stressors, but what maintains this diversity is unclear. Arabidopsis thaliana exhibits high within‐population variation in drought response. One hypothesis is that competition, varying at small scales, promotes diversity in resource use strategies. However, little is known about natural variation in competition effects on Arabidopsis physiology. We imposed drought and competition treatments on diverse genotypes. We measured resource economics traits, physiology, and fitness to characterize plasticity and selection in response to treatments. Plastic responses to competition differed depending on moisture availability. We observed genotype–drought–competition interactions for relative fitness: competition had little effect on relative fitness under well‐watered conditions, whereas competition caused rank changes in fitness under drought. Early flowering was always selected. Higher δ 13 C was selected only in the harshest treatment (drought and competition). Competitive context significantly changed the direction of selection on aboveground biomass and inflorescence height in well‐watered environments. Our results highlight how local biotic conditions modify abiotic selection, in some cases promoting diversity in abiotic stress response. The ability of populations to adapt to environmental change may thus depend on small‐scale biotic heterogeneity.